Global graphics color,a guide to design with color for an international market - Cullen, Cheryl Dangel (U.S.A : ROCK PORT, 2000)
Illustrates how significant color customs are used by different cultures to convey particular meanings to groups of people within that culture.
north american / latin america / western europe / eastern europe / africa / the asian pacific rim / the southwestern pacific.
includes index.
All age.
Keywords: Graphic arts